2019
DOI: 10.1186/s13046-019-1304-y
|View full text |Cite
|
Sign up to set email alerts
|

RNA helicase p68 deploys β-catenin in regulating RelA/p65 gene expression: implications in colon cancer

Abstract: Background RelA/p65 a crucial member of NF-κB signaling pathway plays diverse role in mediating oncogenesis. Limited knowledge prevails on the mechanistic insights of RelA gene regulation. RNA helicase p68 apart from being a vital player of RNA metabolism acts as a transcriptional coactivator of several oncogenic transcription factors including β-catenin and is highly implicated in cancer progression. In this study, we aim to discern the molecular mechanism of how an RNA helicase, p68 deploys a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…In another research, the authors found p68, also named as DDX5, and β-catenin increased RelA mRNA and protein expression. DDX5 was perceived to associate with RelA promoter while β-catenin at the TCF4/LEF (TBE) sites thereby potentiating RelA transcription ( 31 ). DDX27 was also observed to be highly expressed in CRC tissues and increased the proliferation and motility through promote p65 to bind to the promoter region of its target genes ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another research, the authors found p68, also named as DDX5, and β-catenin increased RelA mRNA and protein expression. DDX5 was perceived to associate with RelA promoter while β-catenin at the TCF4/LEF (TBE) sites thereby potentiating RelA transcription ( 31 ). DDX27 was also observed to be highly expressed in CRC tissues and increased the proliferation and motility through promote p65 to bind to the promoter region of its target genes ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…TRAF6 activates NF-κB via the nuclear shuttling effect of p65 in CRC 30 . RNA helicase p68 enhanced NF-κB target genes expression by directly promoting p65 transcription 31 . Our research introduced a new mechanism that helps understand the NF-κB pathway in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted using Trizol reagent (Invitrogen) and processed for real-time PCR as previously described 19 . Briefly, cDNA was prepared, and Real-time PCR was performed using SYBR Green Master Mix (Bio-Rad) in Via7 Real-Time PCR Instrument (Applied Biosystems), described before.…”
Section: Rna Preparation and Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%